Quantitative Determination and Toxicity Evaluation of Aristolochic Acid Analogues in Asarum heterotropoides F. Schmidt (Xixin) and Traditional Chinese Patent Medicines - Suyan Liu; Zhong Xian; Yong Zhao; Lianmei Wang; Jingzhuo Tian; Chen Pan; Jiayin Han; Yushi Zhang; Chunying Li; Yan Yi; Chenyue Liu; Dunfang Wang; et al. (Frontiers Media S.A., 2021)
Asarum (Xixin), which contains analogues of aristolochic acid (AA), is the only species of the genus Aristolochia included in the Chinese Pharmacopoeia 2020. However, the contents and nephrotoxic effects of AA analogs in Asarum (Xixin) and its formulations have not been clarified. An automatic, effective solid phase extraction process and UPLC-MS/MS method were established for the pretreatment and quantitative detection of AA analogues in commercially available traditional Chinese patent medicines. The cytotoxicity and DNA damage induced by five analogues of AA were evaluated by CCK8 using human kidney cells (HK-2) and comet assays. HPLC was used to detect the analogues of AA in Asarum heterotropoides F. Schmidt (Xixin). The results showed that the contents of AA I, AA II, and AA IIIa were below the detection limit, while AA IVa and AL I presented relatively high contents of Asarum heterotropoides F. Schmidt (Xixin), within the range of 66.50-121.03 μg/g and 19.73-43.75 μg/g, respectively. The levels of AA analogues were in the nanogram-per-gram level in the main traditional Chinese patent medicines. AA I and AL I exhibited relatively high cytotoxicity at 48 h in CCK8 assays, while AA II, AA IIIa, and AA IVa showed weak cytotoxicity even at 800-1,000 μM. AA I induced significant pathological alterations and direct DNA damage at 40 mg/kg and 20 mg/kg, respectively. No distinct nephrotoxicity or hepatotoxicity was observed in mice treated with AA II, AA IIIa, AA IVa, or AL I at 40 mg/kg in this study. Consumption of Asarum heterotropoides F. Schmidt (Xixin) with controlled doses and periods is relatively safe as the contents of AA analogues in Asarum heterotropoides F. Schmidt (Xixin) and its formulations were far below those causing acute toxicity in this study. But, the long-term toxicity of Asarum heterotropoides F. Schmidt (Xixin) still needs further study.